ESBL and AmpC β-Lactamase Encoding Genes in E. coli From Pig and Pig Farm Workers in Vietnam and Their Association With Mobile Genetic Elements - Hounmanou, Yaovi Mahuton Gildas; Bortolaia, Valeria; Dang, Son Thi Thanh; Truong, Duong; Olsen, John E.; Dalsgaard, Anders (Frontiers in Microbiology, 2021)
Animals are considered important sources of ESBL/AmpC-producing bacteria in humans. We analyzed indications of transfer of ESBL/AmpC genes between pigs and pig farmers in Vietnam by analyzing whole genome sequences of 114 ESBL/AmpC-producing E. coli isolated from the two hosts, and performed conjugation experiments and plasmid profiling to confirm that such transfer could have happened. ESBL-encoding genes detected in pigs and pig farmers included blaCTX-M-55, blaCTX-M-27, blaCTX-M-65, blaCTX-M-15, blaCTX-M-14, blaCTX-M-3, blaCTX-M-24 and blaCARB-2, and AmpC β-lactamases included blaCMY-2, blaDHA-1 and blaCMY-42. The most frequent ESBL gene, blaCTX-M-55, was carried on plasmid with replicons types IncF, IncX, IncH, IncN, IncR and IncP. The insertion transposases downstream of the blaCTX-M-55 gene were different in plasmids carried by different strains. The second most detected gene, blaCTX-M-27, is found in a stable genetic arrangement with the same flanking transposons seen across strains, and the gene was located on similar conjugal IncF plasmid types, suggesting a horizontal spread of these plasmids. In three strains, we observed a novel blaCTX-M-27 harboring IncF type of plasmid which had not been reported before. Its closest reference in NCBI was the non-ESBL Salmonella Typhimurium plasmid pB71 that might have experienced an insertion of blaCTX-M-27. Our data also point to an emergence of plasmids co-carrying ESBL genes, mcr genes, quinolones and other antimicrobials resistance determinants, and such plasmids require special attention. Plasmids phylogeny confirmed that the blaCTX-M-55 encoding plasmids varied considerably, while those encoding blaCTX-M-27 were closely related. Plasmids harboring both ESBL genes were confirmed to be conjugative and not to differ in transfer efficacy. The isolates carrying the plasmids, even those with plasmids of similar types, showed wide genetic variation with high number of SNPs, suggesting horizontal spread of plasmids into different clonal lines. Their virulence profiles did not confirm to known pathotypes, suggesting that unrelated commensals are a main reservoir for ESBL and AmpC β-lactamases in both humans and pigs. Overall, despite evidence of transferability of plasmids in the analyzed strains, our findings do not support that ESBL-producing E. coli from pigs or their ESBL/AmpC encoding plasmids are commonly spread to workers in close contact with the animals